2021
DOI: 10.1017/s0007114521004177
|View full text |Cite
|
Sign up to set email alerts
|

Do we eat what we buy? Relative validity of grocery purchase data as an indicator of food consumption in the LoCard study

Abstract: The validity of grocery purchase data as an indicator of food consumption is uncertain. This paper investigated 1) the associations between food consumption and grocery purchases using automatically accumulated purchase data, and 2) whether the strength of the associations differed in certain sub-populations. The participants filled in a food frequency questionnaire (FFQ), and a major Finnish retailer issued us with their loyalty-card holders grocery purchase data covering the 1- and 12-month periods preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 40 publications
7
24
0
Order By: Relevance
“…However, our sensitivity analysis showed that the purchase patterns were similar when only those who bought ≥81% of their food from the retailer were included in the factor analysis. This is in line with our previous finding that the proportions of food groups purchased were very similar among customers with high loyalty (22) , and that their purchases reflect the loyalty-card holder's dietary intake (19) . To estimate the similarity of the purchase data with the purchases of the general Finnish population, the average annual expenditure on groceries and non-alcoholic beverages in Finland was 2916 €, and on alcohol and cigarettes 578 € in 2016 (50) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, our sensitivity analysis showed that the purchase patterns were similar when only those who bought ≥81% of their food from the retailer were included in the factor analysis. This is in line with our previous finding that the proportions of food groups purchased were very similar among customers with high loyalty (22) , and that their purchases reflect the loyalty-card holder's dietary intake (19) . To estimate the similarity of the purchase data with the purchases of the general Finnish population, the average annual expenditure on groceries and non-alcoholic beverages in Finland was 2916 €, and on alcohol and cigarettes 578 € in 2016 (50) .…”
Section: Discussionsupporting
confidence: 92%
“…As the data covered an extensive time period, they were more accurate regarding habitual consumption and the inclusion of the seasonal variation of food consumption. We have also previously shown that food purchase data are a valid instrument for ranking consumers according to their self-reported food (19) and beer (20) consumption. Our data included detailed information on thousands of product groups, which enabled regrouping based on the principles most appropriate for the purpose.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The degree to which household-level purchases from the retailer represent individual consumption is unknown. Previous validation studies highlight that agreement between purchases and consumption is likely to vary by loyalty status and household composition [ 54 , 55 ], with higher agreement observed for single-person households [ 54 ]. However, accepted adjustment factors remain lacking.…”
Section: Discussionmentioning
confidence: 99%